COVID‐19 Vaccine‐Associated Cerebral Venous Thrombosis in Germany. Issue 4 (23rd August 2021) - Schulz, Jörg B.; Berlit, Peter; Diener, Hans‐Christoph; Gerloff, Christian; Greinacher, Andreas; Klein, Christine; Petzold, Gabor C.; Piccininni, Marco; Poli, Sven; Röhrig, Rainer; Steinmetz, Helmuth; Thiele, Thomas; et al.
Abstract : Objective: We aimed to estimate the incidence of cerebral sinus and venous thrombosis (CVT) within 1 month from first dose administration and the frequency of vaccine‐induced immune thrombotic thrombocytopenia (VITT) as the underlying mechanism after vaccination with BNT162b2, ChAdOx1, and mRNA‐1273, in Germany. Methods: A web‐based questionnaire was e‐mailed to all departments of neurology. We requested a report of cases of CVT occurring within 1 month of a COVID‐19 vaccination. Other cerebral events could also be reported. Incidence rates of CVT were calculated by using official statistics of 9 German states. Results: A total of 45 CVT cases were reported. In addition, 9 primary ischemic strokes, 4 primary intracerebral hemorrhages, and 4 other neurological events were recorded. Of the CVT patients, 35 (77.8%) were female, and 36 (80.0%) were younger than 60 years. Fifty‐three events were observed after vaccination with ChAdOx1 (85.5%), 9 after BNT162b2 (14.5%) vaccination, and none after mRNA‐1273 vaccination. After 7, 126, 434 first vaccine doses, the incidence rate of CVT within 1 month from first dose administration was 0.55 (95% confidence interval [CI] = 0.38–0.78) per 100, 000 person‐months (which corresponds to a risk of CVT within the first 31 days of 0.55 per 100, 000 individuals) for all vaccines and 1.52 (95% CI = 1.00–2.21) for ChAdOx1 (after 2, 320, 535 ChAdOx1 first doses). The adjusted incidence rate ratio was 9.68 (95% CI = 3.46–34.98) for ChAdOx1 compared to mRNA‐based vaccines and 3.14 (95% CI = 1.22–10.65) for females compared to non‐females. In 26 of 45 patients with CVT (57.8%), VITT was graded highly probable. Interpretation: Given an incidence of 0.02 to 0.15 per 100, 000 person‐months for CVT in the general population, these findings point toward a higher risk for CVT after ChAdOx1 vaccination, especially for women. ANN NEUROL 2021;90:627–639